Raising the bar for causal inference: PLOS Medicine adopts the TARGET guidelines for target trial emulation studies - Lumbard, Helen (PLoS medicine, 2025)
The TARGET guidelines aim to improve transparency and consistency in reporting of observational studies that emulate target trials. In alignment with these goals, PLOS Medicine fully endorses the TARGET guidelines and now asks that new submissions of target trial emulation studies adhere to them.